Albumin coatings for counteracting uremic metabolites effects on host responses to biomaterials - Sharma, Indu; Sharaf, Mehdi Ghaffari; Pawar, Aishwarya; Lockwood, Ethan; Unsworth, Larry D. (Frontiers in Bioengineering and Biotechnology, 2025)
Chronic kidney disease is a progressive condition characterized by a decline in kidney function that is the impetus for an increased retention of uremic metabolites (UMs) in the blood compartment which is correlated with adverse patient outcomes. The inefficient clearance of some UMs using membrane hemodialysis is a significant problem, and adsorptive materials are actively being researched to overcome this issue. Albumin is an abundant serum protein known to bind UMs and minimize non-specific protein adsorption at albumin-modified surfaces: two important aspects for designing modified surfaces for clearing UMs from blood. Herein, we anchored albumin to nanoparticles to understand if UM effects on protein-driven host responses to nanoparticles could be minimized. UM doped platelet-poor plasma was used to characterize protein-initiated clotting kinetics and immunoblot analysis of important protein mediators of the immune, fibrinolytic, and coagulation cascades. The amount of particles and density of adsorbed BSA could return clot formation to that seen for uremic plasma controls, but were unable to return these conditions to that seen for normal plasma. These surfaces significantly lower amounts of adsorbed C3, α1-antrypsin, Protein S, cleavage fragments of fibrinogen, prothrombin, factors XI and XII, and antithrombin compared to bare controls with UMs. However, in almost all cases the effect of UMs still led to dramatic increases in adsorbed proteins, and BSA films only reduced adsorption of IgG, vitronectin, prothrombin and antithrombin compared to normal plasma results. BSA films did ameliorate the effect of nanoparticles in uremic plasma. At these concentrations, these films were unable to adsorb enough UMs to negate their effects. This is an important milestone in the design of hemocompatible surfaces for clearing UMs from the blood.